Autophagic lysosomal reformation depends on mTOR reactivation in H2O2-induced autophagy. (January 2016) - Zhang, Jiqian; Zhou, Wei; Lin, Jun; Wei, Pengfei; Zhang, Yunjiao; Jin, Peipei; Chen, Ming; Man, Na; Wen, Longping
Abstract: Autophagic lysosomal reformation, a key cellular process for maintaining lysosome homeostasis in elevated autophagy, so far has only been reported for cells under certain forms of starvation. For this reason, it is controversial that whether this phenomenon is starvation-specific and its importance in lysosomal regeneration at the late stage of autophagy is often challenged. Here we show that exogenous hydrogen peroxide (H2 O2 ) induced lysosome depletion and recovery characteristic of autophagic lysosomal reformation, and we confirmed the occurrence of autophagic lysosomal reformation after H2 O2 treatment by demonstrating Rab7 dissociation from autolysosomes, recruitment of Phosphatidylinositol 4-phosphate (PI4P) and clathrin to the surface of autolysosomes, and the existence of tubular "pro-lysosome" structures extending from autolysosomes. Similar to starvation, H2 O2 caused an initial deactivation and a subsequent reactivation for mTOR, and mTOR reactivation was essential for ALR. Our results provided a first non-starvation example of autophagic lysosomal reformation and provide evidence for its importance for some autophagic processes other than that of starvation.